The "ROSHE" Nutrition Education Model for Families in Stunting Prevention Efforts - Rosa Riya; M. Naswir; Asni Johari; Solha Elrifda (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
ntroduction: Stunting is a growth disorder in children caused by chronic undernutrition, recurrent infections, and inadequate psychosocial stimulation. A child is classified as stunted when their height-for-age falls more than two standard deviations below the median of the Child Growth Standards. Stunting has serious short-term consequences, including impaired brain development, reduced intelligence, delays in physical growth, and metabolic disturbances. In the long term, it contributes to decreased cognitive and learning performance, weakened immunity, and greater susceptibility to illness. Methods: This study aimed to develop and analyze the impact of implementing the ROSHE nutrition education model on the cognitive abilities and attitudes of families in preventing stunting. The research utilized a Research and Development (R&D) design guided by the ADDIE approach to create the “ROSHE” educational model for families. Data collection involved needs analysis, one-to-one testing, and small-group testing through interviews and observations, while field testing employed validated pre-test and post-test questionnaires. The initial phase focused on analyzing stunting-related issues, followed by contextual and literature-based data gathering relevant to family-centered stunting prevention efforts. Results: During the design stage, the Health Belief Model served as the primary theoretical foundation, integrated with the Social Cognitive Theory (SCT) and the Technology Acceptance Model (TAM). This integration produced a conceptual framework for the initial version of the ROSHE model, which was validated by three experts in information technology, educational technology, and nutrition science. One-to-one and small-group evaluations indicated that the model was easy for families of stunted children to use. Field test results demonstrated an increase in average knowledge and improvements in attitudes after the intervention. The Wilcoxon test yielded a p-value of 0.000, indicating a significant difference in knowledge and attitude changes before and after participation. Conclusion: The ROSHE nutrition education model effectively enhances family knowledge and attitudes in efforts to prevent stunting.